The Insurance Role of Social Security : Theory and Lessons for Policy Reform - Valdivia, Victor (IMF Working Papers; Working Paper ;, 1997)
This paper examines the impact of social security on welfare. The provision of social security reduces precautionary savings and encourages early retirement. Consequently, it lowers aggregate capital, employment, output, and consumption. On the other hand, it also provides old age insurance. This trade-off is examined using a life-cycle general equilibrium model. The paper finds that the current U.S. Social Security system can improve welfare even though the levels of aggregate output, employment, capital, and consumption fall relative to their levels without such a system. The welfare gains arise from insurance against living much longer than expected.